Ratio of catchment to cultivated area for different slopes under runoff farming of sorghum at Hamelmalo, Eritrea - FREZGHI, HURUY; SINGH, BALWAN; OGBAZGHI, WOLDESELASSIE (Journal of Soil and Water Conservation, 2020)
The study was conducted at Hamelmalo Agricultural College, Eritrea, 15°52′21′′ N and 38°27′58′′ E latitude and longitude, respectively and atan elevation of 1274 m above mean sea level with semi-arid climate. The objective of the study was to increase sorghum production by harvesting runoff water from different areas of micro-catchments at different slopes to the cultivated areas. Four treatments with the ratio of catchment to cultivated area as 0:1 (T1), 0.5:1 (T2), 1:1 (T3), and 1.5:1 (T4) were chosen at three slopes 35% (S1), 10 % (S2), and 5% (S3) of the catchment area. A split plot design was used with slope as the main plot and catchment ratios in the sub-plots with three replications.Performance of the four treatments on the cultivated area at S1, S2, and S3 slopes was evaluated in terms of soil moisture conservation. The average volumetric water content in surface profile (0-20 cm) in T1, T2, T3 and T4 at S1 slope was 11.9, 14.6, 17.6 and 20.6 percent, at S2 slope was 11.9, 14.1, 19.3 and 26 percent and at S3 slope was 12, 15.5, 20.5 and 25.6 percent, respectively. The crop yield on cultivated areas receiving runoff from different sized catchments under the three catchment gradients with T4, T3 and T2 increased almost 3, 2.5 and 1.5 fold, respectively over their corresponding control (T1). The study concluded that for optimum grain yield of sorghum the ratio of Catchment: Cultivated Area at S1, S2 and S3 slopes were 0.8: 1; 1.1:1and 2.2:1, respectively